Vestibulocochlear dysfunction in a patient with rheumatoid disease and vasculitis. Issue 6 (June 1991) - Merrin, P K; Macfarlane, D G
Abstract : The case is described of a patient with rheumatoid disease and evidence of vasculitis who developed acute vestibuloauditory dysfunction resulting in total deafness, which was assumed to be secondary to a vasculitic process affecting the vestibulocochlear nerve. Treatment of the underlying vasculitic process, despite effecting a general improvement of the patient's rheumatoid disease, did not significantly improve the auditory dysfunction.